Masalah yang Dihadapi oleh Guru Sejarah dalam Manajemen Kelas di SMAN 7 Tanjungpinang - Mahfuzah Susan Saniah (CAHAYA PENDIDIKAN, 2021)
This research aims to: 1). Knowing why teachers face problems in classroom management on history learning at SMAN 7 Tanjungpinang. 2). Knowing what difficulties teachers face in doing classroom management on history learning at SMAN 7 Tanjungpinang. 3). Know how teachers overcome classroom management problems in history learning at SMAN 7 Tanjungpinang. The method used in this study is a research method with a skinative descriptive approach with the following steps: 1). Determining the location of the research, 2). Determination of informants, 3). Data collection techniques, 4). Data validation techniques, 5) Data processing techniques, 6) Writing. The results of this study are the first, the cause of teacher difficulties in classroom management in historical learning at SMAN 7 Tanjungpinang is from the teacher, student, and infrastructure factors. Second, the thing that causes teacher difficulties in classroom management in learning the history of SMAN 7 Tanjungpinang is the lack of management of places of learning, material management, management of learning resources, and student arrangements. Third, there are several steps taken by teachers in overcoming problems in classroom management, namely finding student problems, finding problems, finding alternatives in problem solving, and getting feed back. With the problem, class management on history learning at SMA N 7 Tanjungpinang, can be resolved well with several stages.